2015
DOI: 10.1631/jzus.a1200260
|View full text |Cite
|
Sign up to set email alerts
|

Pullout capacity of small ground anchor: a least square support vector machine approach

Abstract: This study employs the least square support vector machine (LSSVM) for the prediction of pullout capacity of small ground anchor. LSSVM is firmly based on the theory of statistical learning and uses regression technique. In LSSVM, Vapnik and Lerner (1963)'s ε-insensitive loss function was replaced by a cost function which corresponded to a form of ridge regression. The input parameters of LSSVM were equivalent anchor diameter, anchor embedment depth, average cone tip resistance, average cone sleeve friction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…14 As shown in Figure 6, the experimental result indicated that surface roughness dropped on the whole as the grinding speed increased. According to the least square vector machine algorithm (LS-SVM) 15 and experiment data, a group of prediction data could be obtained. Based on the GA-BP network algorithm, the single factor experiment data were used in training, the corresponding prediction data were obtained for the surface roughness in accordance with the grinding speed.…”
Section: One-dimensional Model Of Surface Roughnessmentioning
confidence: 99%
“…14 As shown in Figure 6, the experimental result indicated that surface roughness dropped on the whole as the grinding speed increased. According to the least square vector machine algorithm (LS-SVM) 15 and experiment data, a group of prediction data could be obtained. Based on the GA-BP network algorithm, the single factor experiment data were used in training, the corresponding prediction data were obtained for the surface roughness in accordance with the grinding speed.…”
Section: One-dimensional Model Of Surface Roughnessmentioning
confidence: 99%
“…Ground anchors are an important load-carrying part that is directly related to the safety of tower construction, economy and rationality 9 , 10 . The effectiveness of ground anchoring mainly depends on the interaction of soil and ground anchors, and its mechanical mechanism of load transfer is often originated from a potential displacement of the anchor or soil 11 . Accordingly, ground anchors can be divided into two types: active and passive.…”
Section: Introductionmentioning
confidence: 99%
“…Ground anchors are an important load-carrying part that is directly related to the safety of tower construction, economy and rationality [9][10] . The effect of ground anchoring mainly depends on the interaction of soil and ground anchors, and its mechanical mechanism of load transfer is often caused by a potential displacement of the anchor or soil 11 . Accordingly, ground anchors can be divided into two types: active and passive.…”
Section: Introductionmentioning
confidence: 99%